Recommendations for Care and Support of Female Rape Victims - Fryszer, Lina Ana; Büttner, Melanie; Etzold, Saskia; Muetzel, Elisabeth; Rall, Katharina; Schellong, Julia; Team of authors at Frauennotruf [Womenʼs Emergency Helpline] Frankfurt; David, Matthias (Geburtshilfe und Frauenheilkunde, 2022)
Introduction According to prevalence studies, at least 5% of all women in the Federal Republic of Germany experience rape during their lifetime. While the effects vary according to the individual, rape has serious consequences for the somatic, psychological, and psychosocial health of the victim. The medical care that is provided to presumed rape victims is of special importance, as this care can have a positive influence on the patientʼs ability to process their experience and engage in healing following such a traumatic event. Furthermore, doctors are the professionals whose help is most often sought in this context. Primary care following rape consists of three aspects: the forensic medical examination, medical care, and psychological care. In this position paper, each of these aspects are discussed in detail. Recommendations for follow-up care are also provided.Methods In a multi-tiered process, a selective literature review was performed and a consensus among representative experts from different areas of specialization was formulated.Goals The goal of this paper is to contribute to the further improvement and standardization of the medical care provided to women who are presumed rape victims.Einleitung In der Bundesrepublik Deutschland erleben laut Prävalenzstudien mindestens 5% aller Frauen in ihrem Leben eine Vergewaltigung. Eine Vergewaltigung hat, individuell unterschiedlich ausgeprägt, gravierende Folgen für die somatische, psychische und psychosoziale Gesundheit Betroffener. Der ärztlichen Versorgung mutmaßlich Stuprum-Betroffener kommt eine besondere Wichtigkeit zu, da diese einerseits den Verarbeitungs- und Heilungsprozess nach einem solchen einschneidenden Ereignis positiv beeinflussen kann und andererseits Ärztinnen und Ärzte in diesem Zusammenhang die am häufigsten konsultierten professionellen Helferinnen bzw. Helfer sind. Die Erstversorgung nach Stuprum setzt sich aus 3 Anteilen zusammen: der medizinisch-forensischen Untersuchung sowie der medizinischen und psychischen Versorgung. Auf die einzelnen Anteile wird detailliert in der Stellungnahme eingegangen. Ebenfalls werden Empfehlungen zur Nachbetreuung getroffen.Methoden Es erfolgte eine selektive Literaturrecherche sowie die Erarbeitung eines Konsensus unter repräsentativen Expertinnen und Experten aus verschiedenen Fachbereichen in einem mehrstufigen Verfahren.Ziele Ziel der Stellungnahme ist es, einen Beitrag zur weiteren Verbesserung und Standardisierung der ärztlichen Versorgung mutmaßlich Stuprum-betroffener Frauen zu leisten.
Keywords: stuprum; rape; sexual violence; primary care; forensic medical examination; psychosocial support